Organisational perspectives on boring prison work: Between emancipation and paranoia. (September 2022) - Mikkelsen, Elisabeth Naima
Boredom may take different forms depending on the setting. However, most existing literature portrays it as a negative phenomenon for both individuals and organisations. While boredom is studied primarily via controlled laboratory experiments and questionnaire-based studies, past research has been criticised for neglecting to understand workers' experiences of boredom in real-world work settings. Drawing on a qualitative case study comprising of interviews with prison officers and ethnographic fieldwork in two Danish prisons, this article explores workers' experience of boredom embedded in specific organisational work practices of repetitive routines, waiting and meaningless tasks. It shows that workers may take an organisational perspective on their experience of boredom, rather than a personal one, acknowledging the tedious features of work but nevertheless emphasising their organisational value. I use a phenomenological approach to sensemaking to deepen the understanding of how workers' protests against boredom may not be only destructive but may sometimes take creative forms, leading to positive organising. Drawing on these findings, I extend our understanding of boredom at work.